Modeling and control of XY table using trajectory adaptive ZPETC / Hashimah Ismail - Ismail, Hashimah (Institute of Graduate Studies, UiTM, 2017)
Trajectory tracking application is widely used in industry especially for manufacturing process. Control systems design for precise and highspeed trajectory tracking is challenging enough as the plant system model transfer function will be presented by non-minimum phase system. In this thesis, a new digital tracking control technique by utilizing feedforward adaptive ZPETC is proposed to solve the non-minimum phase problem. The proposed feedforward controller design was tested and applied on an XY table by simulation and real-time experiment. XY table is a flat surface mechanical system which facilitates horizontal motion in X and Y axes and normally used for machinery. Good controller design can provide precise trajectory motion of both axes and thus minimize the tracking and contour error of the XY table. The XY table plant discretetime models were obtained from input-output experimental data using Matlab system identification toolbox. Sampling time 45 ms was used to get nonminimum phase discrete-time plant model and minimum phase system was obtained using 60 ms sampling time. Minimum phase system was also used to test the usability of the proposed control technique. In this study, adaptive feedforward ZPETC without factorization of zeroes was considered…